2021
DOI: 10.21203/rs.3.rs-260577/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High Frequency of Multidrug-resistant (Mdr) Klebsiella Pneumoniae Harboring Several β-lactamase and Integron Genes Collected From Several Hospitals in the North of Iran

Abstract: Background: Klebsiella pneumoniae is one of the leading causes of hospital outbreaks worldwide. Also, antibiotic-resistant K. pneumoniae is progressively being involved in invasive infections with high morbidity and mortality. The aim of the current study was to determine antimicrobial susceptibility patterns and the incidences of resistance genes (integron types and β-lactamase-encoded genes) among clinical isolates of K. pneumoniae. Methods: In this cross-sectional study, a total of 100 clinical samples were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…In addition, more types and numbers of resistance genes were identified in class 1 integron-positive isolates than in class 1 integron-negative isolates, such as aadA2 (75% vs. 5.65%), bla KPC-2 (77.08% vs. 16.90%), and bla SHV-1 (73.96% vs. 12.68%), which made the class 1 integron-positive group show higher MIC levels for the corresponding antimicrobials. Similar to transposons, class 1 integrons can capture resistance genes from bacteria of various sources (Fluit and Schmitz, 2004;Firoozeh et al, 2019;Farhadi et al, 2021). It plays an important role in resistance gene spreading by means of horizontal gene transfer between bacteria of different species or genera, resulting in the increasing emergence of MDR bacteria, especially clinical pathogens (Fluit and Schmitz, 2004;Firoozeh et al, 2019;Farhadi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, more types and numbers of resistance genes were identified in class 1 integron-positive isolates than in class 1 integron-negative isolates, such as aadA2 (75% vs. 5.65%), bla KPC-2 (77.08% vs. 16.90%), and bla SHV-1 (73.96% vs. 12.68%), which made the class 1 integron-positive group show higher MIC levels for the corresponding antimicrobials. Similar to transposons, class 1 integrons can capture resistance genes from bacteria of various sources (Fluit and Schmitz, 2004;Firoozeh et al, 2019;Farhadi et al, 2021). It plays an important role in resistance gene spreading by means of horizontal gene transfer between bacteria of different species or genera, resulting in the increasing emergence of MDR bacteria, especially clinical pathogens (Fluit and Schmitz, 2004;Firoozeh et al, 2019;Farhadi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to transposons, class 1 integrons can capture resistance genes from bacteria of various sources (Fluit and Schmitz, 2004;Firoozeh et al, 2019;Farhadi et al, 2021). It plays an important role in resistance gene spreading by means of horizontal gene transfer between bacteria of different species or genera, resulting in the increasing emergence of MDR bacteria, especially clinical pathogens (Fluit and Schmitz, 2004;Firoozeh et al, 2019;Farhadi et al, 2021). Twelve groups of 29 complete class 1 integrons were identified in 17 isolates with complete genome sequences.…”
Section: Discussionmentioning
confidence: 99%
“…This was similarly observed in the research carried out by Carl et al [15] when they observed two E. coli isolates that also showed 100% resistance to polymyxin B and colistin. Farhadi et al [16] observed 62.22% resistance of Klebsiella. However, in the work of Naveed-ur-Rehman et al [17], there was 100% sensitivity of Klebsiella pneumoniae to Polymyxin B and that led to the use of the antibiotic to cure eight (8) out of fourteen ( 14) patients (57.1%).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies highlight high frequency of prevalence of MDR Klebsiella pneumoniae with 30-day mortality rate as high as 45% in patients with K. pneumonia BSI. 15,16 28% of Klebsiella and 21% E. coli were detected to be multi drug resistant strains. Klebsiella pneumoniae is notorious for its ability to accumulate and transfer resistance determinants, and it has been well-recognized as a leading causative agent of hospital-based infections over the previous decades.…”
Section: Discussionmentioning
confidence: 99%